EFISIENSI SALURAN PEMASARAN DAN ELASTISITAS TRANSMISI HARGA KOMODITAS TEMBAKAU VIRGINIA DI DESA POHWATES KECAMATAN KEPOHBARU KABUPATEN BOJONEGORO - Badiatud Durroh; Moh Yusuf Dawud (Agros Journal of Agriculture Science, 2024)
The agricultural sector is one of the sectors that has the potential to be developed in the province of East Java. One of them is that tobacco commodity is a pillar for the East Java economy as well as playing a strategic role in the national economy. The purpose of this study was to analyze (1) the marketing channel for virginia tobacco commodities in Pohwates Village, Kepohbaru District, Bojonegoro Regency; (2) marketing channel efficiency for virginia tobacco commodities in Pohwates Village, Kepohbaru District, Bojonegoro Regency; (3) price transmission elasticity of virginia tobacco commodities in Pohwates Village, Kepohbaru District, Bojonegoro Regency. The sampling technique in this study was carried out by simple random sampling for farmer respondents and snowball sampling for trader respondents. Data collection techniques used are observation, interviews & questionnaires, and documentation. The data analysis carried out was descriptive with a qualitative and quantitative approach. The results showed that (1) there were two marketing channels for Virginia tobacco farming in the form of dry/chopped leaves with the final consumer, namely tobacco warehouses; (2) Virginia tobacco marketing in Pohwates Village has been running efficiently, as evidenced by various marketing indicators, namely the analysis of margin calculations, margin distribution, and Farmer’s Share. Margin value on marketing channel 1 is IDR 2,291 and on channel 2 is IDR 3,458. It can be interpreted that marketing channel 1 is more efficient than marketing channel 2; (3) The price transmission elasticity value is IDR 426.71 (more than one) > 1, which means that the marketing of virginia tobacco in Pohwates Village, Kepohbaru District, Bojonegoro Regency is elastic and forms an oligopsony market structure. Keywords: Virginia Tobacco, Marketing Channel, Efficiency, Price Transmission Elasticity INTISARISektor pertanian menjadi salah satu sektor yang berpotensi untuk dikembangan di wilayah Provinsi Jawa Timur. Salah satunya komoditas tembakau menjadi pilar bagi perekonomian Jawa Timur sekaligus memainkan peran strategis dalam kancah perekonomian nasional. Tujuan penelitian ini adalah menganalisis (1) saluran pemasaran komoditas tembakau virginia di Desa Pohwates Kecamatan Kepohbaru Kabupaten Bojonegoro; (2) efisiensi saluran pemasaran komoditas tembakau virginia di Desa Pohwates Kecamatan Kepohbaru Kabupaten Bojonegoro; (3) elastisitas transmisi harga komoditas tembakau virginia di Desa Pohwates Kecamatan Kepohbaru Kabupaten Bojonegoro. Teknik pengambilan sampel pada penelitian ini dilakukan dengan simple random sampling untuk responden petani dan snowball sampling untuk responden pedagang. Teknik pengumpulan data yang dilakukan adalah observasi, wawancara & kuesioner, dan dokumentasi. Analisis data yang dilakukan yaitu deskriptif dengan pendekatan kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa (1) terdapat dua saluran pemasaran usahatani tembakau virginia dalam bentuk daun kering/rajangan dengan konsumen akhir yaitu gudang tembakau; (2) Pemasaran tembakau virginia di Desa Pohwates telah berjalan efisien, dibuktikan dari berbagai indikator pemasaran yaitu analisis perhitungan margin, distribusi margin, dan Farmer’s Share. Nilai margin pada saluran pemasaran 1 sebesar Rp 2.291 dan pada saluran 2 yaitu Rp 3.458. Dapat diartikan bahwa saluran pemasaran 1 lebih efisien dibandingkan saluran pemasaran 2; (3) Nilai elastisitas transmisi harga yaitu sebesar Rp 426,71 (lebih dari satu) >1 dapat diartikan bahwa pemasaran tembakau virginia di Desa Pohwates Kecamatan Kepohbaru Kabupaten Bojonegoro bersifat elastis dan membentuk struktur pasar oligopsoni. Kata kunci: Tembakau Virginia, Saluran Pemasaran, Efisiensi, Elastisitas Transmisi Harga